UDK 677.021.152.001.76 THEORETICAL STUDY OF THE EFFECT OF A BRUSHED DRUM SHAFT ON THE EFFICIENCY OF FLUSH SEPARATION - Abdurahmonov, Jahongir (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
In this article, research was carried out to improve the brush drum-type Lintermachine, which effectively cleans the fluffy product obtained by linting cotton seeds from impurities. In the study, a brush drum that effectively removes lint (fluff) from the saw teeth in a linting machine, a number of brushes located on the drum, and the length of the arc between the intersection and separation of the brushes with the saw teeth and The theoretical studies studied the intersection angles that form them. It was established that the wicker the drum effectively separates the saw teeth without negatively affecting the natural properties of the product.